Epidemics and the Military: Responding to COVID-19 in Uganda. (December 2022) - Parker, Melissa; Baluku, Moses; Ozunga, Bono E.; Okello, Bob; Kermundu, Peter; Akello, Grace; MacGregor, Hayley; Leach, Melissa; Allen, Tim
Abstract: The UN Security Council's response to Ebola in 2014 legitimised militarised responses. It also influenced responses to COVID-19 in some African countries. Yet, little is known about the day-to-day impacts for ordinary citizens of mobilising armies for epidemic control. Drawing on 18 months ethnographic research, this article analyses militarised responses to COVID-19 during, and following, two lockdowns at contrasting sites in Uganda: a small town in Pakwach district and a village in Kasese district. Both field sites lie close to the border of the Democratic Republic of Congo. Although the practice of health security varied between sites, the militarised response had more impact than the disease in these two places. The armed forces scaled back movement from urban conurbations to rural and peri-urban areas; while simultaneously enabling locally based official public authorities to use the proclaimed priorities of President Museveni's government to enhance their position and power. This led to a situation whereby inhabitants created new modes of mutuality to resist or subvert the regulations being enforced, including the establishment of new forms of cross-border movement. These findings problematise the widely held view that Uganda's response to COVID-19 was successful. Overall, it is argued that the on-going securitisation of global health has helped to create the political space to militarise the response. While this has had unknown effects on the prevalence of COVID-19, it has entrenched unaccountable modes of public authority and created a heightened sense of insecurity on the ground. The tendency to condone the violent practice of militarised public health programmes by international and national actors reflects a broader shift in the acceptance of more authoritarian forms of governance. Highlights: Global focus on health security has legitimised militarisation of epidemic control. Ethnographic research reveals impacts of militarizing COVID-19 responses in Uganda. New modes of mutuality were created to resist or subvert regulations being enforced. Unaccountable modes of public authority were entrenched alongside growing insecurity. Embedding military activity in COVID-19 responses strengthened authoritarian rule.